Detection of some Trace Elements in Sera of Detergent Industry Workers - Hamad, Samera H; Kadhim, Nafesa J; Ali, Ismael M (Al-Nahrain Journal of Science, 2011)
The piece of this study describes the estimation of three trace elements (chromium, nickel and vanadium) using Electrothermal atomic absorption spectrometer in twenty two sera samples workers of the detergents industries in Baghdad city. Also, twenty two sera samples were used as a control in this study. It is found that chromium concentrations in the sera samples of workers are with the control cases, vanadium and nickel concentrations are decreased in the sera of workers cases compared to that control cases. The result is analyzed statistically by using ANOVA method to the decide differences between the results at 99% confidence level. It was found that the chromium concentration in the range of ages 15-29 years. are significantly differences ,nickel concentrations in the sera samples of workers in the range of ages 15-29 and 45-58 years are showed significantly differences, and it was found that the differences in the vanadium concentrations in all ranges of ages of workers.